Epithelial–myoepithelial carcinoma of the nasopharynx: A case report and review of the literature - Zhang, Wei; Wang, Xiao-xiao; Wang, Xiao-li; Zhang, Yan; Li, Xiu-feng; Li, Yang; Cai, Yuan-yuan; Ren, Hui-qi; Zhang, Yun-xiang; Hao, Fu-rong (Frontiers in Oncology, 2022)
Background: Epithelial–myoepithelial carcinoma (EMCa) is a rare low-grade malignant tumor that most commonly occurs in the salivary glands, with approximately 320 cases having been reported worldwide. Here, we report the third case of EMCa occurring in the nasopharynx. Rare cases in the breast, pituitary gland, lacrimal gland, nose, paranasal sinus, nasal cavity, trachea and bronchus, lung and even the pleura mediastinalis have also been reported. Histopathology and immunohistochemistry are useful for confirming the diagnosis of EMCa, which is characterized by biphasic tubular structures composed of inner ductal and outer clear myoepithelial cells and stains for different markers in each layer. However, because of the rarity of EMCa, the clinicopathological characteristics and treatment of these patients remain unclear. Case Presentation: We report a rare case of EMCa of the nasopharynx. A 51-year-old man presented with a 5-month history of pain while swallowing and aggravation accompanied by right ear tinnitus lasting for 1 month. Nasopharyngoscopy and magnetic resonance imaging (MRI) of the nasopharynx and neck revealed a 5.6 cm ×3.4 cm ×3.1 cm mass in the nasopharyngeal space, invasion of the right cavernous sinus, and lymph node enlargement in the right retropharyngeal space. On April 17, 2019, based upon the histopathological and immunohistochemical features, a final diagnosis of EMCa of the right nasopharynx was made. The patient underwent concurrent chemoradiotherapy (CCRT), and his symptoms were relieved after treatment. On January 10, 2022, nasopharynx MRI and biopsy revealed local recurrence, but chest and abdominal computed tomography (CT) showed no obvious signs of metastasis. The local recurrence-free survival (LRFS) period was 33 months. Conclusion: To the best of our knowledge, this is the third reported case of EMCa in the nasopharynx and the only case of EMCa in the nasopharynx treated with CCRT, and a partial response was achieved. Therefore, to improve the quality of life and prognosis of patients with unresectable tumors, we believe that CCRT is a suitable option. Further clinical observations are required to elucidate the pathophysiology and prognosis of EMCa.